Blood Glucose and Tingling Sensation in Feet: Chi-Square and Spearman Approach - Wijaya , Wilson Gani; Setyawan, Yuswanto (PROMOTOR, 2025)
This study aims to investigate the relationship between blood glucose levels and tingling sensation in the feet among individuals with suspected diabetic neuropathy using the Chi-Square and Spearman correlation approach. A cross-sectional design was applied involving 100 participants aged 35–65 years selected through purposive sampling. Data were collected using structured questionnaires and fasting blood glucose tests, followed by statistical analysis using SPSS. Results showed a significant association between elevated blood glucose levels and the presence of tingling sensations (p < 0.05). Spearman's test indicated a strong positive correlation (r = 0.682), suggesting that as glucose levels increase, the likelihood of tingling sensations also rises. These findings support the hypothesis that persistent hyperglycemia contributes to peripheral nerve damage, potentially leading to diabetic neuropathy. This research highlights the importance of early detection and glycemic control as preventive measures. Further longitudinal studies are recommended to explore causal mechanisms and clinical interventions.